2013
DOI: 10.4103/2229-516x.112242
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and design of sustained release matrix tablets of metformin hydrochloride: Influence of hypromellose and polyacrylate polymers

Abstract: Aim:The current paper was an attempt to design a sustained release dosage form using various grades of hydrophilic polymers, Hypromellose (hydroxyl-propyl methylcellulose [HPMC] K15M, HPMC K100M and HPMC K200M) and Polyacrylate polymers, Eudragit RL100 and Eudragit RS100 with or without incorporating ethyl cellulose on a matrix-controlled drug delivery system of Metformin hydrochloride.Materials and Methods:Laboratory scale batches of nine tablet formulations were prepared by wet granulation technique (Low she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…The in vitro release studies of the above system indicated that the combination of this material may modify the dissolution rate 39 . An extended release tablet containing metformin was successfully prepared via melt granulation combining the hydrophobic stearic acid and hydrophilic poly(ethylene oxide).…”
Section: Pharmaceutical Formulations For the Delivery Of Metforminmentioning
confidence: 99%
“…The in vitro release studies of the above system indicated that the combination of this material may modify the dissolution rate 39 . An extended release tablet containing metformin was successfully prepared via melt granulation combining the hydrophobic stearic acid and hydrophilic poly(ethylene oxide).…”
Section: Pharmaceutical Formulations For the Delivery Of Metforminmentioning
confidence: 99%
“…Generally, sustained-release dosage forms provide better control of drug levels in plasma, reduce dosage frequency and increase therapeutic efficacy through steady drug delivery. 4 The bioadhesive property of certain polymeric systems has found relevance in drug delivery as a means of prolonging contact time in the various mucosal routes of drug administration. The ability to maintain a delivery system at a particular location for an extended period of time has great appeal for local action as well as systemic drug bioavailability.…”
mentioning
confidence: 99%
“…The most commonly used water insoluble polymers for extended release applications are the ammonium ethacrylate copolymers cellulose derivatives ethyl cellulose and cellulose acetate, and polyvinyl derivative, polyvinyl acetate [15,17,20].…”
Section: Extended Release Dosage Formsmentioning
confidence: 99%